Composite resin susceptibility to red wine staining after water sorption - Catelan, Anderson; Barbosa, Gabriella Lopes de Rezende; Suzuki, Thaís Yumi Umeda [UNESP]; Barreto, Bruno de Castro Ferreira; Giorgi, Maria Cecília Caldas; Goiato, Marcelo Coelho; Santos, Paulo Henrique dos [UNESP]; Aguiar, Flávio Henrique Baggio (My University, 2013)
Color stability of restorative materials is essential for longevity of esthetic composite restoration over time. The aim of this investigation was assess the effect of prior water immersion on the color stability of a composite resin to red wine staining. Seventy disccshaped specimens (6mm x 1.5mm) were carried out and randomized in 7 groups (n = 10), according to distilled water immersion time at 0 (control), 24, 48, 72,120,192, and 240 h. Baseline color was measured according to the ciel*a*b* system using a reflection spectrophotometer(uvc2450, shimadzu).After that, the specimens were storage in red wine for 7 days. Color difference (∆e) after aging was calculated based on the color coordinates before(baseline) and after storage period.Data were subjected to onecway anova(alpha=0.05).The different times of immersion in.Water before to the red wine storage showed similar behavior on the color stability, without statistical difference compared to control group, immersed directly in the wine(p=0.7057).The previous water uptake of composite resin evaluated did not decrease the susceptibility to red wine staining.
Keywords: Composites resins; Physical properties; Color